Congenital lymphatic hypoplasia in unilateral lower limb with abnormal technetium-99m sulphur colloid uptake in both breasts - Padma, Subramanyam (Indian J Nucl Med, 2014)
We present a patient with Meige like lymphedema (left lower limb hypoplasia) with asymptomatic minimal accumulation of Technetium-99m sulfur colloid in bilateral breasts. We attribute the possible pathology to accumulation of interstitial fluid in hypoplastic left lower limb leading to dilatation of the remaining outflow tracts and valvular incompetence. This may be causing reversal of flow from subcutaneous tissues into the dermal plexus involving the breast. Other possibilities include formation of spontaneous lymphovenous shunt or lymphatic intercommunication at lower trunk level as a result of increased pressure leading to minimal lymph accumulation in breasts. Later a mammogram was performed which was found to be normal. MR also confirmed no cisterna chyli abnormalities or aberrant lymphatic channels in lower thorax region that may be the explanation for the abnormal sulphur colloid uptake in both breasts.